Agricultural mechanization in transition farming due to industrialization - a case study of Korea - Ahn, Duck-hyun; Singh, Gajendra; Tang, John C.S.; Gee-Clough, D. (Bangkok : Asian Institute of Technology, 1987)
The relationship between agricultural sector a nd non - agricultural sector is mutually supportive a nd competitive. As a result one sector can not develop without the other sectors support . Industrialization has induced transformation of agricultural system. But industrialization is only a necessary condition for development of agriculture . So a device to increase agricultural productivity should be followed. Agricultural mechanization plays an important role as a catalyst in agricultural development through substituting farm labor and stimulating transformation of agricultural structure. If the basic conditions regulating mechanization are fulfilled agricultural mechanization is feasible in spite of s mall scale farming system. Under the Korean situation 'characterized by small farm scale, relative low purchasing ability and off- farm income opportunities, cooperative operation should be promoted. Agricultural mechanization can be accomplished in collaboration with and concern for the development of the industrial and agricultural sectors and relative production factor endowments. Proposed direction of agricultural mechanization in Korea are as follows, the first step is a development of various income sources so that the saved labor by mechanization can be converted to various income activities. The next step is to accelerate the mobility of production resources to achieve a large scale farming structure using a large and efficient machinery.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Farm mechanization -- Korea